Strategy storytelling to improve the level of listening comprehension in the students of the second grade “A” secondary level at Cristo Rey high school - district José Leonardo Ortiz, province of Chiclayo, region of Lambayeque – 2017 - Garcia Yzquierdo, Edilberto Antonio (2021)
This research work is carried out with the purpose of improving the receptive capacity of the English language, which is oral comprehension in the second grade "A" students from "Cristo Rey" high school in José Leonardo Ortiz district, Chiclayo city, Lambayeque department. Based on Howard Gardner's Linguistic Intelligence where he tells us that if we develop this intelligence through: dialogues, watching and commenting on movies, singing, reading stories, games to increase vocabulary (crosswords, puzzles) and storytellings we can make our students to be able of interact and communicate correctly in a second language. The use of the storytelling strategy will allow the students to motivate the interest to listen and understand what is being communicated, by listening they will learn new sounds, adequate intonations and thus increase their level of oral comprehension to learn a language. The problem was diagnosed when an evaluation was applied and which resulted in low interest in listening, the students felt uncomfortable because they did not understand what they were asked or did not understand the oral texts. This research and subsequent application of the storytelling strategy to improve oral comprehension allowed to improve an optimal result because it was possible to awaken interest in understanding an oral text in English, at the beginning, we had low results, but at the end the results were satisfactory.